2018
DOI: 10.18632/aging.101671
|View full text |Cite
|
Sign up to set email alerts
|

A CREB1/miR-433 reciprocal feedback loop modulates proliferation and metastasis in colorectal cancer

Abstract: Increasing evidence has indicated the prognostic value of miR-433 across a series of malignancy types. However, the underlying mechanisms involved in cancer progression haven’t been sufficiently elucidated. In the present work, we found that miR-433 was downregulated in CRC tissues and cell lines. Ectopic expression of miR-433 obviously suppressed the proliferation, invasion and metastasis activity of CRC cells in vitro and in vivo. CREB1, CCAR1 and JNK1 were highly expressed and negatively correlated with miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 43 publications
4
27
0
Order By: Relevance
“…17 As for in GC, an inhibitor of CREB1, miR-1297, was found to be poorly existed in GC patients and positively correlated with survival of patients. 18 Promotion of CREB1 in cancer has also been evidenced in several tumor cell types involving bladder cancer, 19 colorectal cancer 20 and glioma 21 cells. Likewise, high-expression profiles of CREB1 have also been found in GC cell lines and its downregulation led to declines in growth and migration of SGC-7901 cells.…”
Section: Discussionmentioning
confidence: 97%
“…17 As for in GC, an inhibitor of CREB1, miR-1297, was found to be poorly existed in GC patients and positively correlated with survival of patients. 18 Promotion of CREB1 in cancer has also been evidenced in several tumor cell types involving bladder cancer, 19 colorectal cancer 20 and glioma 21 cells. Likewise, high-expression profiles of CREB1 have also been found in GC cell lines and its downregulation led to declines in growth and migration of SGC-7901 cells.…”
Section: Discussionmentioning
confidence: 97%
“…Several miRNAs, such as miR-134-5p, miR-27a-5p, and miR-342-3p, target the PKG downstream molecule Creb1; novel_circ_000915 can also target Creb1 and function as a ceRNA pair according to our prediction. In colon cancer, miR-433 inhibits Creb1 and exerts an antitumor effect by inhibiting the cell cycle [ 27 ]. Creb1 is also a direct target of miR-122, which can promote cell proliferation and invasion in bladder cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“… 37 , 38 In our study, we identified that CREB1 was upregulated in CRC tissues and cells, and the similar results upon CREB1 in CRC were documented in the previous study. 39 Interestingly, CREB1 was a target of miR-519d-3p. Moreover, the CREB1 protein expression was upregulated in CRC cells treated with co-transfection of both si-BLACAT1 and anti-miR-519d-3p in comparison with transfection of si-BLACAT1 solely in vitro.…”
Section: Discussionmentioning
confidence: 99%